TikTok as a New Media for the Future of Indonesian Creative Work - Dliyaun Najihah; Dina Septiani (INJECT (Interdisciplinary Journal of Communication), 2024)
TikTok is widely favored among numerous individuals as a social media platform. This research seeks to analyze the expansion of TikTok in Indonesia, explore the opportunities it offers to creative professionals in the country, and examine the potential drawbacks and effects associated with uploading short videos on this social media platform. This study is an analytical Systematic Literature Review (SLR) of publication trends related to TikTok, New Media, and Creative Works. The methodology involves scientific mapping through scientometric analysis, qualitative discussions, and bibliometric searches. The study results show that TikTok is one of the digital media in Indonesia that is proliferating. TikTok serves as a new medium for global communication and information exchange, a platform for interaction, sharing, and socializing, a primary destination for users, a social commerce venue, and a portfolio showcase. Indonesian creative workers use TikTok as a promotional and trading medium. However, face-to-face communication through TikTok can reduce the trust of TikTok users when making transactions, conversations, communications, self-actualization and so on. It can also lead to misunderstandings when carrying out long-distance activities without being based on more detailed and specific explanations.